Bank Dividend Policy: Does the ESG Rating Matter? - Rogers, Tammy; Casey, K. Michael (Journal of Leadership, Accountability and Ethics, 2020)
This paper examines the relationship of social responsibility and dividend policy of bank holding companies. Using the Sustainalytics ESG (Environmental, Social, Government) rating and its component scores as measures of social responsibility, the paper uses a variation of Rozeff’s (1982) agency cost/transaction cost tradeoff model to evaluate bank dividend policy and the impact of social responsibility. The paper finds that bank holding companies paying higher dividends that force them into the external markets also have better corporate governance structures in place.